Molecular genetic features of the diabetes mellitus development and the possibility of precision therapy - Tatyana Yu. Demidova; Svetlana G. Zenina (Сахарный диабет)
The purpose of this review is to analyze existing data on the molecular genetic features of the development of type 1 and type 2 diabetes mellitus, gestational diabetes and specific types of diabetes (maturity onset of diabetes of the young, neоnatal diabetes) and to assess the possibility of precision therapy.The etiology of diabetes is heterogeneous, and a genetic predisposition plays a significant role in its development. Genetic studies, conducted in the past few decades, allow us to identify a number of genes that directly affect the development of diabetes. The genetic prerequisites indicate high levels of predictability for the occurrence of type 1 diabetes. The only personalized treatment that is known to date for such patients is insulin therapy. For monogenic specific types of diabetes, genetic testing is a diagnostic factor which allows to prescribe adequate therapy. The molecular genetic characteristics of the development of type 2 diabetes and gestational diabetes are very complex and ambiguous, however, the existing rich data will become the basis for future recommendations for the prevention, diagnosis and personalized treatment.